2009
DOI: 10.1063/1.3077262
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent fluorescence decay lifetimes of the phosphor Y3(Al0.5Ga0.5)5O12:Ce 1%

Abstract: The decay time of the phosphor YAG:Ce is temperature dependent. Selective incorporation of gallium into the YAG:Ce matrix permits tuning the temperature at which quenching begins. Also, the size of the phosphor particle and processing method affect this characteristic. We describe one such situation in which quenching of the combustion synthesized nanophosphor Y 3 (Al 0.5 Ga 0.5) 5 O 12 :Ce 1% was observed from ambient to 125 C. By signal averaging of laser excited fluorescence, temperature uncertainties range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…from tens of kHz to tens of MHz). This is in sharp contrast to the thermographic luminophores based on rare-earth-doped oxides 9,13,16,41,42 , which are characterized by much slower emission that is typically in the ms-range. Furthermore, the absorption coefficients of tin halides for the UV-A range (315-400 nm, convenient for optical excitation) are high, and they are comparable to the bandgap absorption values (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…from tens of kHz to tens of MHz). This is in sharp contrast to the thermographic luminophores based on rare-earth-doped oxides 9,13,16,41,42 , which are characterized by much slower emission that is typically in the ms-range. Furthermore, the absorption coefficients of tin halides for the UV-A range (315-400 nm, convenient for optical excitation) are high, and they are comparable to the bandgap absorption values (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…[16][17][18] Therefore, much effort has been spent on investigating the thermal performance of high-power LED packages as well as phosphors. [19][20][21][22][23][24][25][26] Fan et al 25) compared conventional and thermal-isolated phosphor coatings by both experiments and finite-element simulations. They found that the surface temperature of the thermal-isolated phosphor coating layer was 16.8 C lower than that of the conventional packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphor-coated white light emitting diodes (LEDs) are widely used for white light illumination due to their high brightness, energy efficiency, and low cost. However, phosphors have a long photoluminescence lifetime (∼60 ns), which limits the LED modulation bandwidth to ∼5 MHz. , More recently, there have been numerous efforts to find alternatives such as quantum dots, , polymer blends, and perovskites to replace phosphors. However, getting the right color rendering index is difficult, and this approach involves replacing all existing white LED lights.…”
mentioning
confidence: 99%